Evaluación de la actividad antioxidante del extracto de las flores de Ruellia Tuberosa l (Petunia Silvestre) - Pambi Balcázar, Priscila Vanessa (2015)
This research activity assessed hydroalcoholic extract of the flowers of Ruellia tuberosa L. radical scavenger as compared to a synthetic antioxidant (ascorbic acid).To make an objective assessment of the quality of Ruellia tuberosa L. and therefore establish the real value of it, evaluation was carried out by analytical procedures. For this purpose in the present work Ruellia tuberosa L. flowers was studied of the gardens of the Technical University of Machala establishing the chemical components and antioxidant activity. The samples were subjected to extraction to ethanol 70°, the resulting extract was analyzed by gas chromatography coupled to mass spectrometry (GCMS).The analysis by gas chromatography of the underivatized sample and the comparison of existing mass spectra in the digital library Wiley, allowed the detection of aromatic compounds, carbonyl compounds, vitamins, carboxylic acids and long chain esters. Additionally some chemical parameters were evaluated by spectrophotometric methods and the antioxidant activity was tested in vitro.